Adaptive superelement modeling for progressive collapse analysis of reinforced concrete frames. (15th November 2017) - Weng, J.; Tan, K.H.; Lee, C.K.
Highlights: A new adaptive super-element procedure for progressive collapse analysis of 2D RC frames is proposed. A new procedure for super-element rigid body rotation correction is suggested. An error indicator is developed to monitor the propagation of nonlinear zone. Advantages of the proposed procedure demonstrated by numerical examples. Abstract: A new adaptive superelement procedure for progressive collapse analysis of 2D reinforced concrete frames under column removal scenario is proposed. Superelement formulation is employed to reduce the computational cost. In addition, a new procedure for rigid body rotation correction is proposed to improve the accuracy of the superelement formulation. An error indicator is developed to monitor the propagation of the nonlinear zone during analysis. The adaptive analysis procedure is then formed by combining the error indicator with a reliable member and substructure collapse identification algorithm. Numerical examples are given to demonstrate the accuracy, robustness and efficiency of the modeling procedure. As the work involves establishing a novel concept to reduce computational effort when simulating the whole process of collapse, the authors only consider the impact energy of falling objects in a quasi-static manner through the use of dynamic increase factors, thereby obviating the need for time-consuming nonlinear structural dynamic analysis.